Anterior Crossbite, Dental Arch Dimensions, and Later Need for Orthognathic Surgery in 6-Year-Old Children with Unilateral Cleft Lip and Palate. (September 2014) - Heliövaara, Arja; Leikola, Junnu; Rautio, Jorma
Objective: Six-year-old children with unilateral cleft lip and palate were examined to compare the prevalence of anterior crossbite and dental arch dimensions of those who later needed orthognathic surgery with the prevalence of those who did not. Design: Retrospective longitudinal study. Patients: A total of 68 consecutive nonsyndromic patients with unilateral cleft lip and palate (44 boys, 24 girls). Main Outcome Measures: Children with unilateral cleft lip and palate whose palates had been closed in one stage by the Veau-Wardill-Kilner or Cronin-Brauer V-Y pushback techniques were analyzed from dental casts taken at a mean age of 6.1 years (range, 5.7 to 6.8 years) before orthodontic treatment or bone grafting. The need for orthognathic surgery in these patients was determined from hospital records at the mean age of 18.2 years (range, 15.6 to 20.2 years). Student's t test and chi-square test were used in statistical analyses. Results: The prevalence of anterior crossbite was 62% (one or both central incisors in full crossbite). The prevalence was higher (75% versus 53%) in children later needing orthognathic surgery (28 of 68, 41%), but the difference was not significant. Nor were there significant differences in dental arch measurements between children who later needed osteotomies and those who did not or between the two modifications of the primary palatal pushback operations. Conclusions: The prevalence of anterior crossbite and the dental arch dimensions did not differ between 6-year-old children with unilateral cleft lip and palate who later needed orthognathic surgery and those who did not.